Proceedings of the 2023 International Symposium on Children and Youth Health and Well-being (2024)
Bridging theory and practice, the up-to-date evidence from these proceedings marks an important contribution to the advancement of children and youth health and well-being professions in the issues of technology, health, stress, inclusion, and resilience. The empirical research reported here examines the perceptions of parents, social workers, counselors, and other helping professionals concerning their awareness of child protection and parent-child relationships. These proceedings serve as a catalyst for action, enabling researchers and practitioners to reference and view the newest research through the lenses of diverse themes that focus on children and youth health and well-being, and to impact the younger population at micro and macro levels. This key text has several important features: 1. It emphasizes the impact of digital technology on well-being among children and young people in this digital age, and how to involve different stakeholders who can help to respond to emergent and existing challenges. 2. It introduces learning disabilities and issues in the field of mental stress and the biopsychology of developmental needs in school settings in addressing the UN Sustainable Development Goals. 3. It advances health knowledge and care practice through practice-oriented research, establishing new benchmarks in health care work, identifying its possibilities and constraints. 4. It enriches knowledge in the field of safeguarding for adults, including parental involvement in identifying and responding to children and youth well-being.

Counterfeit Opportunities in Luxury Fashion - Gasulla-Tortajada, Elena; Duarte, Paulo; Silva, Susana C. (2025)
Counterfeiting in luxury fashion presents unique opportunities for brands. While it negatively impacts them by diluting exclusivity, it also affects consumer psychology in unexpectedly positive ways. Authentic consumers may feel pride in being copied, enhancing their perceived status by owning something only a few can possess. Additionally, counterfeits act as free marketing tools, increasing brand awareness on a scale not otherwise accessible, especially for niche or inconspicuous luxury brands. Moreover, counterfeiting offers an opportunity for differentiation through sustainability. Counterfeiters, focused on low-cost production, often cannot commit to sustainable and ethical standards. Luxury brands can leverage this by emphasizing their commitment to sustainability, distancing themselves from counterfeits. Strategically, this allows brands to attract consumers who previously purchased counterfeits, converting them into loyal customers of authentic products. This chapter explores how luxury fashion brands can leverage these dual dynamics to strengthen their market position.

As Fontes e as Causas da Fraca Protecção das Comunidades Locais no Ecossistema dos Projectos de Investimento Sobre Recursos Naturais. - Rafael, Angelo (2024)

Law and Development Research Network - MACHVA, ALMEIDA ZACARIAS; Rafael, Angelo; MAY, YDUAN DE OLIVEIRA (2025)
Este livro é resultado do I International Meeting da Law and Development Research Network (LDRN) ou Rede de Pesquisa Direito e Desenvolvimento. As temáticas do encontro internacional foram os objetivos do desenvolvimento sustentável, o desenvolvimento e a inclusão socioeconômicos. O evento foi organizado pelo grupo de pesquisa Direito e Sociedade Econômica (DISE), que completa uma década, orientado à pesquisa e à solução de problemas socioeconômicos sob a ótica jurídica. Está vinculado ao Programa de Pós-Graduação em Direito da Universidade do Extremo Sul Catarinense (PPGD/UNESC), localizado em Criciúma, Santa Catarina, Brasil. O evento contou com o apoio institucional da Universidade São José (USJ, Macau-China), da Universidade Eduardo Mondlane (UEM, Moçambique) e da UNESC. Participaram do comitê científico Prof. Dr. Almeida Zacarias Machava (UEM); Prof. Dr. Ângelo Patrício Rafael (USJ); Prof. Dra. Camila Villard Duran, ESSCA School of Management, França; Prof. Dr. Fernando de Magalhães Furlan, UNICEPLAC, Brasil; e Prof. Dra. Rúbia Carneiro Neves, Universidade Federal de Minas Gerais, Brasil. A coordenação-geral coube ao Prof. Dr. Yduan de Oliveira May, UNESC, coordenador do DISE e da LDRN. Cumprimenta-se o Prof. Dr. Ansoumane Douty Diakité (USJ) pelo prefácio, no qual discorre com generosidade suas impressões das atividades da LDRN e a ordenação temática deste livro.

Guide to Street Art in Macau. - Simões, Filipa (CURB Center for Architecture and Urbanism, 2023)

語文童樂學前語文學習卡 -- 花兒級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 葉芽級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文兒歌集 -- 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

語文童樂學前語文學習卡 -- 果子級 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

《學會閱讀》叢書第二輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

《學會閱讀》叢書第一輯 - 鄭佩芸; 麥紫均 (聖若瑟大學出版社, 2022)

Java面向对象程序设计 - 梁胜彬 (清华大学出版社, 2023)
结合实用案例讲解Java语法、面向对象程序设计技术和核心API。 全书共10章，内容涵盖Java概述、Java语法基础、面向对象基础、面向对象高级技术、 Java API、异常处理机制、Java I/O流、多线程、Java GUI编程和Java网络编程等知识要点。案例丰富，以JDK 17和IntelliJ IDEA等流行的开发环境为依托，力求让读者通过案例 掌握Java编程技术。另一个特色是在阐释专业内容的同时自然融入思政元素， 具有鲜明的时代性和引领性。 可作为普通高等院校计算机、软件工程、人工智能等专业“面向对象程序设计”“Java程序设计”课程的教材，也适 合编程爱好者自学和培训使用。

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by ...

Computerized Systems for Diagnosis and Treatment of COVID-19 - Lobo Marques, Joao Alexandre; Fong, Simon James (Springer International Publishing, 2023)
Keywords: Artificial Intelligence; Biofeedback; Computerized Diagnostic Support; Covid-19; Signal and Image Processing

Memory and Identity: the proceedings of the 28th ASEACCU Annual Conference - Morgan, Stephen (USJ University Press, 2023)

The Inner Harbour - Background Document on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour – Policy Recommendations on the Revitalization of Macau’s Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2014)

The Inner Harbour Vernacular Heritage - Soares, Nuno (CURB-Center for Architecture and Urbanism, 2018)

(Un)directed Reading: Selected Students' Work Directed Reading 2020/21 University of Saint Joseph, Macao, China - Olga Ng Ka Man, Sandra (University of Saint Joseph, 2023)
Keywords: Literature

ARTECH2017: Proceedings of the 8th International Conference on Digital Arts - Caires, Carlos; Cardoso, Jorge Carlos; Lipovka, Aleksei; Bidarra, José; Pimentel, Lúcia (Association for Computing Machinery, 2017)

Book of Proceedings of ARTeFACTo 2022 Macao, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities - Estadieu, G; Martins de Abreu, F.; Caires, Carlos; Fernandes Marco, A. (IEEE, 2023)

De Portugal a Macau: Filosofia e Literatura no Diálogo das Culturas - Natário, Maria Celeste; Espadinha, Maria Antónia (Universidade do Porto, Faculdade de Letras, 2017)

Macao’s mangroves - Tagulao, Karen; Chan, Sek Kiu (University of Saint Joseph, 2020)

Os índios potiguara: memória, asilo e poder - Simões, José Manuel (Coleção mediaXXI, 2013)

Jornalismo e Qualidade no Mundo de Expressão Portuguesa - Camponez, Carlos; Simões, José Manuel; Christofoletti, Rogério (University of Saint Joseph, 2022)
"Jornalismo e Qualidade no Mundo de Expressão Portuguesa"propõe uma análise sobre a paisagem do jornalismo nos oitopaíses de língua oficial portuguesa - Portugal, Angola, Brasil, Cabo Verde, Moçambique, Guiné-Bissau, São Tomé e Príncipee Timor-Leste - e na Região Autónoma Especial de Macau. Olivro é uma reflexão sobre a legislação, o plano jurídico-constitucionalque enquadra os media no espaço lusófono, os contextosde mercado, as especificidades inscritas em fatoreshistóricos e económicos, em percursos políticos, bem comosobre as relações entre os media e os jornalistas e estes e opoder regulador do Estado.Os trabalhos reunidos nesta obra escrita por autores que partilhamentre si um dos idiomas mais falados do planeta, mostram as diferentes realidades do jornalismo no espaço dalíngua portuguesa, nomeadamente as suas redes de conhecimento, de empenho na promoção da qualidade da informação, de intercompreensão entre povos e culturas, de novas einovadoras formas de parcerias sociais com vista à partilha e àconstrução de mundividências.

Epidemic analytics for decision supports in COVID19 crisis - Lobo Marques, Joao Alexandre; Fong, Simon (Springer, 2022)
Covid-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting against the virus, enormously tap on the power of AI and its data analytics models for urgent decision supports at the greatest efforts, ever seen from human history. This book showcases a collection of important data analytics models that were used during the epidemic, and discusses and compares their efficacy and limitations. Readers who from both healthcare industries and academia can gain unique insights on how data analytics models were designed and applied on epidemic data. Taking Covid-19 as a case study, readers especially those who are working in similar fields, would be better prepared in case a new wave of virus epidemic may arise again in the near future.

Succession in Chinese family business: transgenerational transmission of social capital in Macao - Phillips, Jenny O. L. (USJ Theses and Dissertations, 2022)
Macao is well known for its gaming industry. However, there are also many traditional small-to-medium enterprises which are family-owned and run. There is no doubt that social capital is one of the key competitive advantages that family businesses possess, particularly when it comes to Chinese businesses with strong family values that emphasize the importance of trustworthiness and guanxi (relationships). As opposed to other forms of capital, social capital cannot be passed from one generation to another through the will of the incumbents. So, how is social capital passed on in family businesses from one generation to the next? Based on an in-depth study of five cases of successful family businesses in Macao, this research identified the forms of social capital present in business families and the succession process of these firms. From the generalizations drawn from the five cases, a theoretical framework is proposed to understand the intergenerational transmission of social capital in Chinese family businesses
Keywords: China Macau (Special Administrative Region); Family-owned business enterprises

Interaction design for a contemporary learning and teaching environment: promoting independent learning at the primary level - Chan, Ka Chi (USJ Theses and Dissertations, 2022)
The world is perpetually changing, and the COVID-19 pandemic has taught us that the future is full of unforeseen challenges and potentialities. What are the implications of the advancement in technology on education? How are teachers coping with contemporary educational expectations? Is there a need to redesign the learning environment? What is the exact nature of the forces driving such a change? Is there anything we can learn from successful innovations around the globe? The goals of this dissertation include designing a learning/teaching app and redesigning classroom furniture for primary-level education. A design thinking methodology is used, working through the phases of empathizing, defining, ideating, prototyping and testing the two potential designs
Keywords: Design; Interaction analysis in education; Interactive multimedia

Retrieving the Sense of the Sacred: a Paradigm of Silence in the Liturgy - Wong, Lee Chun (USJ Theses and Dissertations, 2021)
Keywords: Catholic Church; Liturgy Theology; Religious aspects Catholic Church; Silence

Pilgrimage Christian and Secular: a Phenomenological Approach - Yuan, Haojun (USJ Theses and Dissertations, 2021)
In the light of the many kinds of journeys that have been considered pilgrimages, this book uses phenomenology as a method to examine the claim that pilgrimage is a journey to the ‘center’ during which pilgrims seek meaning s for themselves. First, by analyzing a phenomenology of Christian pilgrimage, this work attempts to identify what commonalities, as well as differences, exist between Christian pilgrimage and secular pilgrimage in terms of ‘natural attitude’. Next, by using a phenomenological method, such as transcendental reduction, the distinction between these two types of pilgrimage could be clarified that the happiness sought in Christian pilgrimage is both intentionally spiritual and sustainable, while primarily intellectual or sensory in secular pilgrimage. Lastly, this work seeks to establish whether or not ‘being at leisure’ is the primary element for pilgrims whose aim is to attain an understanding of happiness during a pilgrimage
Keywords: Christian pilgrims and pilgrimages; Phenomenology

Student engagement, higher education, and social justice: beyond neoliberalism and the market - Bramley, Corinna; Morrison, Keith (Routledge, 2023)
"Student engagement is a catch-all term, irresistible to educators and policy makers, and serving many agendas and purposes. This ground-breaking book provides a powerful theory of student engagement, rooted in critical theory and social justice. It sets out a compelling argument for student engagement to promote social justice and to repel neoliberalism in, and through, higher education, addressing three key questions: -Student engagement in what? -Student engagement for what? -Student engagement for whom? The answers draw on Habermas, Honneth, Gramsci, Foucault, and Giroux in examining ideology, power, recognition, resistance, and student engagement, with examples drawn from across the world. It sets out key features, limitations and failures of neoliberalism in higher education, and indicates how student engagement can resist it. Student engagement calls for higher education institutions to be sites for challenge, debate on values and power, action for social justice, and for students to engage in the struggle to resist neoliberalism, taking action to promote social justice, democracy, and the public good. This book is essential reading for educators, researchers, managers and students in higher education, social scientists and social theorists. It is a call to reawaken higher education for social justice, human rights, democracy and freedoms"--
Keywords: Active learning; Education, Higher; Neoliberalism; Social aspects; Social justice and education

China-Africa: emerging relations - Sousa, Ivo Carneiro de; Diakite, Ansoumane Douty; Iwaloye, Ojo Olukayode (Saint Joseph Academic Press, 2011)
Keywords: Africa China Congresses; China Africa Congresses; Relations

Book of Proceedings of ARTECH 2021 - 10th International Conference on Digital and Interactive Arts (Hybrid Praxis – Art, Sustainability & Technology) - Lopes, Maria Manuela; Lopes, Paulo Bernardino; Araújo, António; Olivero, Lucas Fabian; Marcos, Adérito Fernandes (2021)

Suicide prevention in schools: are Macau's teachers prepared? - Días, Javier Suárez; Morrison, Keith (Macau Inter-University Institute, 2005)
Keywords: China Macau (Special Administrative Region); Prevention; Students; Suicidal behavior; Suicide; Teenagers

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2007)

A guide to teaching practice - Cohen, Louis; Manion, Lawrence; Morrison, Keith; Wyse, Dominic (Routledge, 2010)
Keywords: Great Britain; Student teaching; Teachers; Training of

Research Methods in Education - Cohen, Louis; Manion, Lawrence; Morrison, Keith (Routledge, 2013)

Managing complex change in school: engaging pedagogy, technology, learning and leadership - Garcia, Alejandro Salcedo; Morrison, Keith (Routledge, 2014)
Keywords: EDUCATION / Educational Policy & Reform / General; EDUCATION / Evaluation; EDUCATION / Leadership; Educational change; Educational leadership; Educational technology

Implementing cross-curricular themes - Morrison, Keith (2018)

School leadership and complexity theory - Morrison, Keith (Routledge/Falmer, 2002)
Keywords: Complex organizations; Educational leadership; School management and organization

Causation in educational research - Morrison, Keith (Routledge, 2009)
Keywords: Causation; Education; Research

Taming randomized controlled trials in education: exploring key claims, issues and debates - Morrison, Keith (Routledge, Taylor & Francis Group, 2021)
"There is a recent surge in the use of randomized controlled trials (RCTs) within education globally, with disproportionate claims being made about what they show, 'what works', and what constitutes the best 'evidence'. Drawing on up-to-date scholarship from across the world, Taming Randomized Controlled Trials in Education critically addresses the increased use of RCTs in education, exploring their benefits, limits and cautions, and ultimately questioning the prominence given to them. While acknowledging that randomized controlled trials do have some place in education, the book nevertheless argues that this place should be limited. Drawing together all arguments for and against RCTs in a comprehensive and easily accessible single volume, the book also adds new perspectives and insights to the conversation; crucially, the book considers the limits of their usefulness and applicability in education, raising a range of largely unexplored concerns about their use. Chapters include discussions on: The impact of complexity theory and chaos theory Design issues and sampling in randomized controlled trials Learning from clinical trials Data analysis in randomized controlled trials Reporting, evaluating and generalizing from randomized controlled trials. Considering key issues in understanding and interrogating research evidence, this book is ideal reading for all students on Research Methods modules, as well as those interested in undertaking and reviewing research in the field of education"--
Keywords: Clinical trials; Education; Educational indicators; Research Data processing; Research Methodolgy

Research methods in education - Morrison, Keith; Cohen, Louis; Manion, Lawrence (Routledge, 2018)

Replication research in education: a guide to designing, conducting and analysing studies - Morrison, Keith (Routledge, 2022)
"Providing an overview of key issues in theory and practice, Replication Research in Education is designed to identify and discuss the benefits and challenges facing replication studies in education. Both clear and practical, this ground-breaking volume covers how to introduce, develop, conduct, report and discuss these studies, and the issues they raise for policy and practice. Bridging theory and practice, this book considers what replication research should look like, how it should be conducted and how to judge when it has been successful. It enables researchers to plan and conduct studies successfully, from their earliest stages through to completion. This key text: brings together in a single volume, existing issues, claims and counter-claims, discourses and practices of replication introduces, covers, and extends this field of research, indicating its possibilities and limits expands and adds to existing discussions and practices will enable researchers to design, conduct, evaluate and critique studies. The comprehensive and exhaustive coverage of issues and practices within Replication Research in Education make it a "must read" for all novice and experienced educational researchers who are considering, conducting, and reviewing replication studies in education"--

Classical theism and Buddhism: connecting metaphysical and ethical systems - McNabb, Tyler Dalton; Baldwin, Erik Daniel (Bloomsbury Academic, 2022)
"As an atheistic religious tradition, Buddhism conventionally stands in opposition to Christianity, and any bridge between them is considered to be riddled with contradictory beliefs on God the creator, salvific power and the afterlife. But what if a Buddhist could also be a Classical Theist? Showing how the various contradictions are not as fundamental as commonly thought, Tyler Dalton McNabb and Erik Baldwin challenge existing assumptions and argue that Classical Theism is, in fact, compatible with Buddhism. They draw parallels between the metaphysical doctrines of both traditions, synthesize their ethical and soteriological commitments and demonstrate that the Theist can interpret the Buddhist's religious experiences, specifically those of emptiness, as veridical, without denying any core doctrine of Classical Theism. By establishing that a synthesis of the two traditions is plausible, this book provides a bold, fresh perspective on the philosophy of religion and reinvigorates philosophical debates between Buddhism and Christianity"--
Keywords: Buddhism; Comparative studies; Relations Theism; Theism

Design Thinking associated with R&D: Process Management and Knowledge Transfer for the Creative Industries - Cerejo, Joana; Barbosa, Álvaro (LAP LAMBERT Academic Publishing, 2014)
The difficult task of innovation is a key facet of Research & Development (R&D) institutions. To Design, innovation is to make the project technically feasible, economically viable, merchandising interesting and emotionally engaging. Design Thinking integrated with R&D organizations can foster the relationship between Universities and new markets. By addressing these topics, this book researches new emerging design methods and provide an overview of Design Thinking tools that can be applied in an early stage of the R&D research process to produce meaningful results. It is taken into account that design, through Design Thinking, extends to the experience that costumers/users have with products/services or even multidimensional experiences, which is a relevant input for R&D innovation development. In fact, the establishment of coherent guidelines for the Design Thinking process is a very complex task, due to its interdisciplinary requirements, that convey many diverse mindsets. The main focus of this book is creating an analysis toolkit that enables non-specialist and specialist users to perform high-quality design solutions.

A cognitive semantic study of biblical Hebrew: the root šlm for completeness-balance - Leong, Andrew Chin Hei (Studies in semitic languages and linguistics, 2021)
"Semantic studies of the Biblical Hebrew verb "whole" have been influenced by those of its most invoked nominal form "whole". In this volume Andrew Chin Hei Leong shows that the concepts of balance, alliance, and completeness form the basic semantic structure of "whole". Previous studies on "whole" employed either historical or textual methodology, which has been dominant in biblical lexical studies. In addition to these methods, in Leong develops a systematic semantic methodology from Cognitive Semantics and Frame Semantics, to demonstrate that it is balance, rather than completeness, that is the most central concept in holding the semantic network together"--
Keywords: Bible; Hebrew language; Language, style; Semantics; Shlm (The Hebrew root)

The Role of Metaxy in the Political Philosophy of Eric Voegelin - Duraj, Jarosław (Peter Lang US, 2021)
This book is a study of Eric Voegelin (1901-1985) and of the role played by metaxy in his vision of political philosophy. Metaxy, already defined by Plato as the "in-between" matrix of the human condition, is for Voegelin a powerful notion that symbolizes the intermediate state in which man experiences diverse and opposing tensions such as the ones between immanence and transcendence or mortality and immortality. The metaxy constitutes the realm of the divine-human mutual participation (methexis), and its locus resides in human consciousness (nous), there where the divine reality manifests itself as the origin of being. Being the field of intermediation between opposing forces, man has to keep the balance of consciousness in order to differentiate the noetic and pneumatic dimensions and so attune his life to the divine ground of being. This book claims that for Voegelin metaxy shapes the possibility of the philosophical, historical, political and religious orientation in life. Indeed, Voegelin’s approach deserves recognition as an option adequate for addressing the intellectual challenges engendered by modern and postmodern philosophies.

John Henry Newman and the development of doctrine: encountering change, looking for continuity - Morgan, Stephen (The Catholic University of America Press, 2021)
"In focusing on the gestation of "An Essay on the Development of Christian Doctrine" (1845), John Henry Newman's last work as an Anglican and presaging his transition to Catholicism, this book examines how Newman accounted for doctrinal continuity in the face of evidence of change in the history of the church"--

Sacred and the Everyday: Comparative Approaches to Literature, Religious and Secular - Morgan, Stephen (USJ Press, 2021)

Bioethics : ethics of life - Gomez, Fausto B. (University of Saint Tomas Publishing House, 2021)

Responsible Entrepreneurship. How to Write a Business Plan (Chinese-English Version) - Rothlin, Stephan; Myers, T. A; Thompson, M (University of International Business and Economics Press, 2015)

Pekinger Nachtgespräche: Gott und die Welt in China (Nighttalks in Beijing. God and the World in China) - Rothlin, Stephan; Achten, Peter (Fromm Verlag, 2018)

International Business Ethics: Focus on China - Rothlin, Stephan; McCann, Dennis (Springer-Verlag, 2016)
This book addresses an essential need felt by many who seek to promote best business practices in China and East Asia – namely the need for culturally appropriate instructional materials (basic information, case studies and ethical perspectives) that will allow managers and entrepreneurs to understand and embrace the challenge of moral leadership in business. In an era characterized by globalization and the increasing importance of the economies of China, India, Japan and SE Asia, international business ethics must reflect the concerns of the people living and working in this area, the moral and spiritual traditions that have nurtured them and their specific contributions to sustainable development. This book presents twenty important case studies, taken from newsworthy events of the past few years, in which Asians and others have attempted to respond to this challenge. Each case study has been selected and shaped in order to highlight various aspects of doing business in Asia, starting with basic principles and moving on to the specific responsibilities that businesses have towards their various stakeholders. The authors contend that the best way to appreciate the relevance of Asian moral and spiritual traditions is to determine their specific contribution to virtue ethics, where the ancient traditions of both East and West converge in their focus on the qualities of moral leadership that form the basis of best business practice. Exploring the case studies will enable readers to appreciate the continued relevance of these ethical perspectives in Asian business. Best business practice clearly involves learning to do business and playing the game according to the rules; but the necessity of playing by the rules is not likely to become clear until one takes up the path that leads to a virtuous life in business, developing a moral character chiefly based on integrity.

Assimetrias de Género. Ensino e Liderança Educativa - Correia, Ana (Fundação Manuel Leão, 2009)
Keywords: DLCRE

Lusofonia, encruzilhadas culturais, Actas da Conferência sobre Lusofonia - Correia, Ana; Sousa, Ivo (Saint Joseph University Press, 2011)

Spatial Analysis Techniques Using MyGeoffice®: - Negreiros, João Garrott Marques (Advances in Geospatial Technologies, 2018)

Predictive Models for Decision Support in the COVID-19 Crisis - Marques, João Alexandre Lobo; Gois, Francisco Nauber Bernardo; Xavier-Neto, Jose; Fong, Simon James (SpringerBriefs in Applied Sciences and Technology, 2021)
COVID-19 has hit the world unprepared, as the deadliest pandemic of the century. Governments and authorities, as leaders and decision makers fighting the virus, enormously tap into the power of artificial intelligence and its predictive models for urgent decision support. This book showcases a collection of important predictive models that used during the pandemic, and discusses and compares their efficacy and limitations. Readers from both healthcare industries and academia can gain unique insights on how predictive models were designed and applied on epidemic data. Taking COVID19 as a case study and showcasing the lessons learnt, this book will enable readers to be better prepared in the event of virus epidemics or pandemics in the future.

Perspectives on Inclusion - Correia, Ana; Couzens, Donna; Ho, Ka Lee Carrie (University of Saint Joseph, 2019)
In an inclusive education system, educators engage with increasing their understanding of individual differences, especially in regard to learning, and develop and adjust learning and assessment tasks and contexts in ways that make them accessible and appropriate for all students regardless of starting ability levels, interests, learning strengths and weaknesses. In inclusive schools, diverse approaches to learning are valued and all learners are challenged and supported to be successful in their learning goals. Macao has begun the journey to develop an increasingly inclusive education system. This book has been written as the journey is beggining and explores some of the different perspectives twoard inclusion and interpretaions of "inclusive education" within Macao's education systems and the wider community at this time. The main aims of the research presented in this book are to understand the different views and roles of staff in Macao schools and in the wider community. The book raises questions about how inclusion in Macao might unfold and identifies areas where efforts may be needed to progress inclusive education.

Historical Space in Macao - Pinheiro, Francisco Vizeu (IACM : Jiangnam University, 2016)

O português dos Tongas de São Tomé. In Oliveira, Márcia Santos Duarte; Araujo, Gabriel Antunes. (orgs.) O português na Africa atlântica - Baxter, A. N. (Humanitas/FAPESP, 2018)

Steps of Greatness: Geopolitics of OBOR, Ed. University of Macau. - Leandro, Francisco José (University of Macau, 2018)

Translation into Portuguese of the work Macau Days - a tri-lingual book (English, Portuguese, Chinese) that includes a series of poetic texts by Brian Castro and artworks by John Young, 2017 in collaboration with the J.M. Coetzee Centre for Creative Practice and the EU Centre for Global Affairs, University of Adelaide, Australia. - Morais, I. (A-A-Publishing, 2018)